Memory and the Jesus tradition - Kirk, Alan (The reception of Jesus in the first three centuries, 2018)
Abbreviations -- Preface -- 1. Memory and Media: Towards a New History of the Tradition -- PART ONE: Formation of the Jesus Tradition -- 2. Social and Cultural Memory -- 3. Cultural and Cognitive Approaches to the Gospel Tradition -- 4. The Memory-Tradition Nexus in the Synoptic Tradition:Memory, Media, and Symbolic Representation -- 5. The Formation of the Synoptic Tradition: Cognitive and Cultural Approaches to an Old Problem -- PART TWO: Memory and Manuscript -- 6. Memory and Manuscript: Gerhardsson Revisited -- 7. Manuscript Tradition as a Tertium Quid: Orality and Memory in Scribal Practices -- 8. Memory, Scribal Media, and the Synoptic Problem -- PART THREE: Memory and Historical Jesus Research -- 9. The Memory of Violence and the Death of Jesus in Q -- 10. Memory Theory and Jesus Research -- 11. Cognition, Commemoration, and Tradition: Memory and the Historiography of Jesus Research -- PART FOUR: Memory in 2nd Century Gospel Writing -- 12. The Johannine Jesus in the Gospel of Peter: A Social Memory Approach -- 13. Tradition and Memory in the Gospel of Peter -- Bibliography -- Index of References -- Index of Authors